La religión en la Unión Europea - Petschen Verdaguer, Santiago (UNISCI Discussion Papers, 2008)
Our reflexive presentation on the situation of religion in the European Union is divided into three parts. First, we explain the lack of an explicit recognition of Europe’s Christian roots. Secondly, we analyze the principles for relations with religions that the EU has included in the Lisbon Treaty. Third, we will cover how the EU de facto contacts the religious communities and dialogues with them.